Strategies in recommending influenza vaccination in Europe and US - Caterina Rizzo; Giovanni Rezza; Walter Ricciardi (Taylor & Francis Group, 2018)
There is potential for influenza vaccine programmes to make a substantial impact on the disease burden. The World Health Organization (WHO) has identified young children, pregnant women, persons with chronic medical conditions, and the elderly as being at risk for severe influenza disease and therefore important groups to be considered for influenza vaccination. Applying the methodology of scoping review of grey and scientific literature we described the European and the US approach to influenza vaccine prevention. Although vaccination remains the most effective means of reducing the incidence and severity of influenza, vaccine uptake in many European countries remains suboptimal (i.e. 45.5% in the elderly, 24% in health care workers, from 49.8% in patients with chronic medical conditions, median 23.6% in pregnant women) and vaccine strategies are not harmonized in particular with regard to vaccinating healthy children. Whereas in the US the vaccine strategies are more standardized across states and vaccine coverage are higher than those reported in EU on average. The integration of different strategies is crucial in order to increase influenza vaccine coverage: public health authorities should encourage healthcare workers to vaccinate themselves, as target category, and to recommend seasonal influenza vaccination to people in the target groups; there should also be structured communication campaigns on influenza and influenza vaccines, directed specifically at these target groups, and an adequate and sustainable funding is also an important factor to achieve higher vaccination coverage rates.